Perioperative management of haemophilia B: A critical appraisal of the evidence and current practices. Issue 6 (27th July 2017) - Neufeld, E. J.; Solimeno, L.; Quon, D.; Walsh, C.; Seremetis, S.; Cooper, D.; Iyer, N. N.; Hoxer, C. S.; Giangrande, P.
Abstract : Background: While there is substantial literature addressing the principles of general management of haemophilia, literature on perioperative management of haemostasis is scarce. Objective: The aim of this study was to better understand perioperative management among congenital haemophilia B patients (without inhibitors) and to gain insights into real‐world surgical practices. Method: A systematic literature review, with an emphasis on haemophilia B, was conducted using EMBASE ®, Medline ® and the Cochrane Library. Studies from 1974 to June 2015 were accessed, and 132 studies were eligible for the full‐study review. An international expert panel with five haematologists and one surgeon reviewed the resulting literature and provided further insights. Results: The literature review revealed that documented experience in the perioperative management of bleeding risk in haemophilia B patients is relatively scarce. Therefore, the review was amended to provide a comprehensive overview of the perioperative management for haemophilia A and B patients; the expert panel applied a particular focus to haemophilia B. Several gaps were identified in the literature including the lack of consensus on defining surgery in terms of bleeding risk, optimal factor levels during surgery and lack of robust evidence on surgical outcomes. The ensuing discussions with the expert panel provided validation of some of the results from the systematic literature review and proposed future directions for perioperative management. Suggestions included collaboration with haemophilia treatment centres (HTCs) to collect real‐world data on perioperative management, establishing the need for optimal factor level monitoring practice, and the appropriate adoption of extended half‐life products in clinical settings.